The effect of grid skewness on non-unified compact residual distribution methods for scalar advection diffusion problems - Aminnuddin, Hazim Fadli; Ismail, Farzad; Mohammed, Akmal Nizam; Abdullah, Kamil (Penerbit Akademia Baru, 2020)
In this paper, the newly developed residual distribution (RD) method called the Flux- Difference approach is combined with the Galerkin method to solve the advectiondiffusion equation in separate (non-unified) manner. It is due to the incapability of variation grid skewness in finite volume. This Flux-Difference RD method maintains a compact stencil and the whole process of solving advection–diffusion do not require additional equations. In order to improve the order of accuracy losses by the classic RD schemes, the present scheme will be tested using non-unified manners. The numerical results show that the Flux-Difference RD method preserves second-order accuracy up to about skewness 0.4 but drops to about 1.5 orders accurate when grid skewness is 0.6.